2020
DOI: 10.1021/acsami.0c10293
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance, Solution-Processable Thermally Activated Delayed Fluorescent Organic Light-Emitting Diodes Realized via the Adjustment of the Composition of the Organoboron Acceptor Monomer in Copolymer Host Materials

Abstract: Organic polymers that exhibit features pertinent to functioning as host materials for thermally activated delayed fluorescence (TADF) emitters have considerable potential in solution-processable organic light-emitting diodes (OLEDs), allowing simple, low-cost, and large-area applications. In particular, polymer hosts have superior characteristics, including facile functionality to introduce various electron donor and acceptor entities, the ability to uniformly disperse and contain small molecular dopants, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…11 External quantum efficiency diagrams of devices (a), and information about the synthesized part (b) with polymers as host materials in recent years. [14][15][16]19,23 the homopolymer P4CzCN-PA-assisted solution-processed OLEDs exhibited a high EQE of 20.9%, which demonstrates the efficient host property of such polymer material. However, after introducing a bulky BCz unit as a copolymer monomer, the efficiency of the devices sharply decreased.…”
Section: Electroluminescent Propertiesmentioning
confidence: 90%
See 1 more Smart Citation
“…11 External quantum efficiency diagrams of devices (a), and information about the synthesized part (b) with polymers as host materials in recent years. [14][15][16]19,23 the homopolymer P4CzCN-PA-assisted solution-processed OLEDs exhibited a high EQE of 20.9%, which demonstrates the efficient host property of such polymer material. However, after introducing a bulky BCz unit as a copolymer monomer, the efficiency of the devices sharply decreased.…”
Section: Electroluminescent Propertiesmentioning
confidence: 90%
“…Thus, beside the above basic requirements, an excellent host for a solutionprocessable device put forward high demands for molecular design, especially the film-forming properties. [14][15][16][17][18][19][20][21] Shao et al reported a series of novel bipolar polymer hosts based on electron-transporting arylphosphine oxide and carbazole units. Based on these polymer hosts, a TADF device with SpiroAC-TRZ, t4CzIPN and TPAPQ as the guest as blue, green and red emitters achieved external quantum efficiencies as high as 15.8%, 17.1% and 10.1%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Because  int is determined by photoluminescence (PL) quantum yield ( PL ), exciton utilization efficiency ( r ), and carrier balance factor (), tremendous efforts have been devoted to exploring luminescent materials with high values in these aspects. Considerable current research interest is focused on purely organic luminescent materials with thermally activated delayed fluorescence (TADF), owing to their excellent theoretical  r values of 100% by virtue of reverse intersystem crossing (RISC) process (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The twisted electron donor (D)-acceptor (A) structures of TADF emitters may also bring about bipolar carrier transport ability and thus a high  value.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy to note that the EQE of pBP-PXZ:CBP exhibits no roll-off when the luminance is less than 200 cd m −2 and just 3% decrease at 500 cd m −2 . The EQE can still be maintained above 19% at 1000 cd m −2 , which represents the best efficiency among TADF polymer-based OLEDs so far under high luminance (Figure 6c) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] . Those results clearly demonstrate that fine-tuning the polymer backbone structure is significant for improving the overall performances of OLEDs.…”
Section: Electroluminescent Propertiesmentioning
confidence: 99%